A Study on Trace Metal Pollution in the Gadilam River Basin, Tamil Nadu, India - Prasanna, Mohan Viswanathan; Chidambaram, S.; Nagarajan, R.; Aruchunan, Elayaraja; Rajalingam, S. (IK international publishing house Pvt Ltd, New Delhi., 2009)
To understand the variation of trace metals such as Iron (Fe), Lead (Pb), Nickel (Ni), Bromide(Br), Iodide (I) and Aluminium (Al) in the study area after the monsoon period, samples were collected and analyzed. The concentration levels of different parameters have been compared with the WHO (1993) standard. Interpretation of data shows that some trace metals such as Al, Ni and Pb exceed the acceptable limit of WHO (1993) standard.